(untitled) (Eurasian Journal of Engineering and Technology, 2024)
This article provides information on the series and ratings of three-phase squirrel-cage asynchronous motors used in an agricultural enterprise. The amount of active and reactive power consumed by an agricultural enterprise in 2023-2024 was also analyzed, and a proposal was made to compensate for reactive power.